THE EFFECT OF EMPOWERING LEADERSHIP ON INTRINSIC MOTIVATION: THE ROLE OF PSYCHOLOGICAL EMPOWERMENT AS A MEDIATION - Khaidir Syahrul (Journal of Leadership in Organizations, 2020)
This research aims to investigate the human resources managment within the government which requires a reliable and competent leadership. A leadership categorized as the concept of empowering when the leader shares direction, a support system, friendly, synergizing, and providing exemplary examples to his subordinates. Employees who feel empowered by the leader would increase their motivation in work. This would increase psychological side of the employee’s cognitions such as a meaningfulness, the competence, a self-determination, and the effect. This research is focused on the process of testing hypotheses and is aimed to examine the effect of empowering leadership’s motivation in the field of work. It is mediated by psychological empowerment. The data used in this study was a questionnaire. This study was used four-stage hypothesis test of Baron and Kenny (1986). The result indicates that empowering leadership has a positive effect on intrinsic motivation , and psychological empowerment partially mediates the positive effect of empowering leadership in supporting intrinsic motivation.